2019
DOI: 10.1186/s42269-019-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum incubation time for formation of Pseudomonas aeruginosa and Streptococcus pyogenes biofilms in microtiter plate

Abstract: Pseudomonas aeruginosa and Streptococcus pyogenes are the most common pathogens to humans and are able to form a biofilm following ineffective precautionary approach. Biofilm is defined as a surface-attached community of bacterium embedded in an extracellular matrix which leads to tremendous problems in the environment, among humans and animals. This study aims to investigate the ability of P. aeruginosa and S. pyogenes to form biofilms in 96-well plate before further study in antibiofilm will be done. Initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…Typhimurium biofilm on the ES surface ( Kim et al., 2016 ). Similarly, it has been suggested that wood encourages biofilm formation because of its porosity and absorbency, which can entrap organic material and bacteria ( Adetunji and Isola, 2011 ; Al-kafaween et al., 2019 ). Moreover, moisture retention on the ES could also account for the greater viability of S. Typhimurium at low temperatures because the eggs were stored while still wet ( Rizk et al., 1966 ).…”
Section: Resultsmentioning
confidence: 99%
“…Typhimurium biofilm on the ES surface ( Kim et al., 2016 ). Similarly, it has been suggested that wood encourages biofilm formation because of its porosity and absorbency, which can entrap organic material and bacteria ( Adetunji and Isola, 2011 ; Al-kafaween et al., 2019 ). Moreover, moisture retention on the ES could also account for the greater viability of S. Typhimurium at low temperatures because the eggs were stored while still wet ( Rizk et al., 1966 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that temperature, nutrients and other components in media affected the attachment of microorganisms to the surfaces of various materials (Hood and Zottola, 1997;Iversen et al, 2004). Study by (Al-kafaween et al, 2019b) showed that the E. coli produced biofilm on day 3 and day 5 in Brain heart infusion (BHI) and Luria broth (LB) at OD 0.05 and OD 0.1 (Al-kafaween et al, 2019). Studies have used TSB for Staphylococcus and Pseudomonas species but this depends on growing condition of microorganisms and optical density (Nyenje et al, 2013;Stepanovi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…or nonadherent [NA = OD ODC)]. ODC was referred to the density of the negative control (Al-kafaween et al, 2019;Al-kafaween et al, 2019a;Nyenje et al, 2013).…”
Section: Biofilms Analysesmentioning
confidence: 99%
“…1-The onset: clinical symptoms culminate in up to 4 days, and mainly manifested through severe pain, this period is equivalent and just refer to the incubation period of Pseudomonas aeruginosa [8].…”
Section: Discussionmentioning
confidence: 99%